The role of cerebro placental ratio as a predictor of adverse perinatal outcome in uncomplicated term pregnancies - Gupta, Nidhi; Agarwal, Mohita; Akanksha; Kapoor, Abhivyakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of the study was to study role of cerebro placental ratio (CPR) as a predictor of adverse perinatal outcome in uncomplicated term pregnancies. Methods: This prospective observational study took place at the Department of Obstetrics and Gynecology in SNMC Agra. We enrolled 140 uncomplicated antenatal cases with gestational age between 37 to 41 weeks, based on specific inclusion and exclusion criteria. Each participant underwent comprehensive assessments, including history-taking, examinations, and ultrasound color Doppler evaluations. We then analyzed perinatal outcomes in correlation with CPR. Results: Adverse perinatal outcomes i.e., asphyxia and NICU admissions were found to be significantly higher in patients with CPR<1. We also observed APGAR<7 at 1 and 5 minutes, cord blood ABG with pH<7.3, pO2<50, PCO2>45 in patients with CPR<1. Conclusions: CPR serves as a noninvasive means to identify fetal compromise in seemingly healthy pregnancies, aiding in the decision-making process regarding the mode of delivery. Clinical significance-CPR can assist in stratifying at risk pregnancies, subsequently influencing decisions regarding the mode and place of delivery.